Production of the plant polyketide curcumin in Aspergillus oryzae: strengthening malonyl-CoA supply for yield improvement. Issue 7 (3rd July 2019) - Kan, Eiichiro; Katsuyama, Yohei; Maruyama, Jun-ichi; Tamano, Koichi; Koyama, Yasuji; Ohnishi, Yasuo
ABSTRACT: The filamentous fungus Aspergillus oryzae was recently used as a heterologous host for fungal secondary metabolite production. Here, we aimed to produce the plant polyketide curcumin in A. oryzae . Curcumin is synthesized from feruloyl-coenzyme A (CoA) and malonyl-CoA by curcuminoid synthase (CUS). A. oryzae expressing CUS produced curcumin (64 μg/plate) on an agar medium containing feruloyl- N -acetylcysteamine (a feruloyl-CoA analog). To increase curcumin yield, we attempted to strengthen the supply of malonyl-CoA using two approaches: enhancement of the reaction catalyzed by acetyl-CoA carboxylase (ACC), which produces malonyl-CoA from acetyl-CoA, and inactivation of the acetyl-CoA-consuming sterol biosynthesis pathway. Finally, we succeeded in increasing curcumin yield sixfold by the double disruption of snfA and SCAP ; SnfA is a homolog of SNF1, which inhibits ACC activity by phosphorylation in Saccharomyces cerevisiae and SCAP is positively related to sterol biosynthesis in Aspergillus terreus . This study provided useful information for heterologous polyketide production in A. oryzae . Graphical abstract: : The plant polyketide curcumin was produced in a recombinant Aspergillus oryzae strain. Strengthening malonyl-CoA supply was effective for yield improvement.